Peptide reactivity associated with skin sensitization: The QSAR Toolbox and TIMES compared to the DPRA. (August 2016) - Urbisch, D.; Honarvar, N.; Kolle, S.N.; Mehling, A.; Ramirez, T.; Teubner, W.; Landsiedel, R.
Abstract: The molecular initiating event (MIE) of skin sensitization is the binding of a hapten to dermal proteins. This can be assessed using the in chemico direct peptide reactivity assay (DPRA) or in silico tools such as the QSAR Toolbox and TIMES SS. In this study, the suitability of these methods was analyzed by comparing their results to in vivo sensitization data of LLNA and human studies. Compared to human data, 84% of non-sensitizers and sensitizers yielded consistent results in the DPRA. In silico tools resulted in 'no alert' for 83%–100% of the non-sensitizers, but alerted only 55%–61% of the sensitizers. The inclusion of biotic and abiotic transformation simulations yielded more alerts for sensitizers, but simultaneously dropped the number of non-alerted non-sensitizers. In contrast to the DPRA, in silico tools were more consistent with results of the LLNA than human data. Interestingly, the new "DPRA profilers" (QSAR Toolbox) provided unsatisfactory results. Additionally, the results were combined in the '2 out of 3' prediction model with in vitro data derived from LuSens and h-CLAT. Using DPRA results, the model identified 90% of human sensitizers and non-sensitizers; using in silico results (including abiotic and biotic activations) instead of DPRA results led to a comparable high predictivity. Highlights: Comparison of in chemico and in silico tools based on an extensive data base In silico data were more consistent with LLNA data than DPRA. DPRA data were more consistent with human data than in silico . The new "DPRA profilers" of the QSAR Toolbox provided unsatisfactory results. In silico or DPRA combination in IATA, predicts human data better than LLNA.